Visible-Light-Promoted Radical Cyclization of N-Arylvinylsulfonamides: Synthesis of CF3/CHF2/CH2CF3-Containing 1,3-Dihydrobenzo[c]isothiazole 2,2-Dioxide Derivatives - Vytla, Devaiah; Kaliyaperumal, Kumargurubaran; Velayuthaperumal, Rajeswari; Shaw, Parinita; Gautam, Raj; Mathur, Arvind; Roy, Amrita (Synthesis, 2021)
A photocatalyzed and highly efficient trifluoromethylation of N-arylvinylsulfonamides using commercially available CF3SO2Cl as the trifluoromethyl radical source under blue LEDs is reported. The reaction proceeds through radical cyclization under mild conditions. An investigation of the substrate scope is performed to establish a general, synthetically useful protocol for the synthesis of novel trifluoromethylated 1,3-dihydrobenzo[c]isothiazole 2,2-dioxides in moderate to high yields. This method is also successfully applied for the synthesis of difluoromethylated and trifluoroethylated 1,3-dihydrobenzo[c]isothiazole 2,2-dioxides in good to excellent yields.
Keywords: N-arylvinylsulfonamides; fluoro alkyl radicals; visible light; radical cyclization; 1,3-dihydrobenzo[c]isothiazole 2,2-dioxides